Generation of THz frequency using panda ring resonator for THz imaging - Jalil, M. A. (2012)
In this study, we have generated terahertz (THz) frequency by a novel design of microring resonators for medical applications. The dense wavelength-division multiplexing can be generated and obtained by using a Gaussian pulse propagating within a modified PANDA ring resonator and an add/drop filter system. Our results show that the THz frequency region can be obtained between 40-50 THz. This area of frequency provides a reliable frequency band for THz pulsed imaging.